PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS - Nyoman Pongga Wikantha; Ni Putu Riasning; Ni Nengah Seri Ekayani (Jurnal Riset Akuntansi Warmadewa, 2023)
This study aims to analyze the influence of cash turnover, accounts receivable turnover, inventory turnover, working capital turnover, and liquidity on the profitability of manufacturing companies in the metal sub-sector from 2017 to 2021. The data were obtained from publicly available financial reports. Using purposive sampling technique, the researchers obtained 8 samples over a 5-year period, totaling 40 data points. The analytical method employed in this study is multiple linear regression, with t-tests used to examine the coefficients of partial regression and the F-test to assess the collective influence at a 5% significance level. The results of the analysis indicate that cash turnover, working capital turnover, and liquidity have a positive and significant impact on profitability, while accounts receivable turnover and inventory turnover have a negative and significant influence on profitability. This research provides a better understanding of the factors that affect a company's profitability and can assist management in making strategic decisions related to cash management, accounts receivable, inventory, working capital, and liquidity to enhance overall profitability.